1994
DOI: 10.1002/etc.5620130604
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation, biotransformation and DNA binding of pahs in feral eel (Anguilla anguilla) exposed to polluted sediments: A field survey

Abstract: Samples of sediment and eel taken from six sites in Amsterdam with different levels of water pollution were analyzed for 16 parental PAHs In addition, biliary PAH metabolites and hepatic PAH‐DNA adducts were determined in the eel to evaluate biomomtoring techniques for PAH exposure There was a clear difference between PAH profiles in sediments and eel Mainly two‐ and three‐ring PAHs were detected in eel, whereas four‐ring PAHs predominated in the sediments Because PAH bioaccumulation was highest in eel from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 28 publications
3
15
0
Order By: Relevance
“…However, there are no recent data available for these sites. Van der Oost et al (1994) reported highest 1-OHPyr bile concentrations of approximately 8000 ng/ml (measured by SFS) in eel (Anguilla anguilla) caught in 1991 from freshwater sites near Amsterdam. The mean level of 1-OHPyr in eel collected in 2011 from the river Rhine in Germany near the Dutch border was 3160 ng/ml (measured by HPLC-FL) (Kammann et al, 2014).…”
Section: Comparison With Other Studiesmentioning
confidence: 98%
See 1 more Smart Citation
“…However, there are no recent data available for these sites. Van der Oost et al (1994) reported highest 1-OHPyr bile concentrations of approximately 8000 ng/ml (measured by SFS) in eel (Anguilla anguilla) caught in 1991 from freshwater sites near Amsterdam. The mean level of 1-OHPyr in eel collected in 2011 from the river Rhine in Germany near the Dutch border was 3160 ng/ml (measured by HPLC-FL) (Kammann et al, 2014).…”
Section: Comparison With Other Studiesmentioning
confidence: 98%
“…PAH metabolites as biomarker has been determined in a variety of marine, estuarine and fresh water fish species, such as English sole (Collier and Varanasi, 1991), plaice (Richardson et al, 2004), flounder (Ariese et al, 1993;Beyer et al, 1996;Eggens et al, 1996;Kopecka et al, 2006;Vethaak et al, 2011), dab (Kammann, 2007;Vethaak et al, 2009), Atlantic cod (Beyer et al, 1996;Aas et al, 2000), Atlantic hagfish (Sundt et al, 2011), feral finfish (Hellou et al, 2006), eelpout (Tairova et al, 2012), brown bullhead (Yang and Baumann, 2006), trout (Escartín and Porte, 1999a), eel (Van der Oost et al, 1994;Ruddock et al, 2003;Gorbi and Regoli, 2004;Nagel et al, 2012;Kammann et al, 2014), and red mullet (Escartin and Porte, 1999b;Martínez-Gómez et al, 2013). The concentration of PAH metabolites in the bile fluid with dab and flounder as target species has become part of international monitoring programmes, such as the OSPAR Joint Assessment and Monitoring Programme (JAMP) (OSPAR Agreement 2008-09; Technical Annex 2: PAHspecific biological effects monitoring; OSPAR, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Pyrene is produced by many pyrolytic and petrogenic processes [43]. It is regarded the best general indicator of PAH exposure in fish [44, 45]. Although pyrene is an extremely widespread and common contaminant, the presence of other PAH metabolites in fish bile can provide additional information about the possible origin of parent compounds.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the differences in tissue PAH concentration was not as noticeable in the two populations as was the case in the sediment samples. Such contradictory tissue and sediment chemistry profiles are not entirely unexpected (Varanasi and Stein 1991; van der Oost et al 1994b; Soclo et al 2008). This could be due to greater bioavailability of LMW compounds (Nye and Witt 1995), or due to the lower efficiency of teleosts in metabolizing LMW PAHs than HMW PAHs (Schnell et al 1980; Varanasi and Stein 1991).…”
Section: Discussionmentioning
confidence: 98%
“…In fact, sediment PAH levels were more reflective of the DNA damage levels in the liver. Others have documented this discrepancy in studies of liver DNA damage and tissue chemistry (van der Oost et al 1994a; van der Oost et al 1994b) and concluded that adduct measurement is a better marker of exposure than tissue PAH concentrations (Meador et al 1995; French et al 1996). This result stresses the importance of obtaining environmental data to infer the actual exposure levels of organisms in field studies.…”
Section: Discussionmentioning
confidence: 99%